2022
DOI: 10.4103/aja202183
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutation in ODF2 causes multiple morphological abnormalities of the sperm flagella in an infertile male

Abstract: Numerous genes have been associated with multiple morphological abnormalities of the sperm flagella (MMAF), which cause severe asthenozoospermia and lead to male infertility, while the causes of approximately 50% of MMAF cases remain unclear. To reveal the genetic causes of MMAF in an infertile patient, whole-exome sequencing was performed to screen for pathogenic genes, and electron microscope was used to reveal the sperm flagellar ultrastructure. A novel heterozygous missense mutation in the outer dense fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Belonging to the outer dense fibers (ODFs) family, ODF2 is an accessory cytoskeletal structure that safeguards the sperm tail from shear forces [28,29]. It has been reported that patients with ODF2 deficiency and asthenozoospermia exhibit multiple abnormalities in sperm flagella morphology (MMAF) [30]. Based on our study, it seems that the decreased expression in the two genes is related to testicular inflammation and reduced spermatogenesis processes in iNOA patients, as the blue module had negative correlation with the turquoise.…”
Section: Discussionmentioning
confidence: 63%
“…Belonging to the outer dense fibers (ODFs) family, ODF2 is an accessory cytoskeletal structure that safeguards the sperm tail from shear forces [28,29]. It has been reported that patients with ODF2 deficiency and asthenozoospermia exhibit multiple abnormalities in sperm flagella morphology (MMAF) [30]. Based on our study, it seems that the decreased expression in the two genes is related to testicular inflammation and reduced spermatogenesis processes in iNOA patients, as the blue module had negative correlation with the turquoise.…”
Section: Discussionmentioning
confidence: 63%
“…Despite the number of proteins making up the centrosome, and its importance in sperm differentiation and flagellum formation, very few centrosomal proteins have been linked to MMAF in humans -so far only CEP135 [34], CEP148 [35] or DZIP1 [36]. Moreover, some major axonemal proteins with an accessory location in the centrosome, such as CFAP58 [37] and ODF2 [38,39], have also been reported to be involved in MMAF syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the number of proteins making up the centrosome, and its importance in sperm differentiation and flagellum formation, very few centrosomal proteins have been linked to MMAF in humans – so far only CEP135 [34], CEP148 [35] or DZIP1 [36]. Moreover, some major axonemal proteins with an accessory location in the centrosome, such as CFAP58 [37] and ODF2 [38, 39], have also been reported to be involved in MMAF syndrome. Other centrosomal proteins lead to MMAF in mice, these include CEP131 [40] and CCDC42 [41].…”
Section: Introductionmentioning
confidence: 99%